KUALITAS FISIK DAN KIMIA DEDAK PADI DENGAN LEVEL PEMBERIAN TEPUNG DAUN NANGKA BELANDA YANG BERBEDA - Tabita N. Ralahalu; Shirley Fredriksz; Stenny Lambatir; Rajab Rajab (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The nature of rice bran is easily damaged, it is necessary to seek a way to overcome this problem. The addition of antioxidants is one way of prevention, one of which is by using Dutch jackfruit leaf flour. This study was conducted to determine the physical and chemical quality of rice bran with different levels of Dutch jackfruit leaf powder. The study was conducted using a completely randomized design (CRD) with 4 treatments, where there were 3 replications in each treatment. The treatments that were tried were as follows: DNB0 (Rice bran with 0% Dutch jackfruit leaf flour) ; DNB1 (Rice bran with 0.6% of Dutch jackfruit leaf flour) ; DNB2 (Rice bran by giving 1.2% Dutch jackfruit leaf flour) ; DNB3 (Rice bran with 1.8% Dutch jackfruit leaf powder). Qualitative data such as odor and color of rice bran were discussed descriptively, while quantitative data such as weight, number of lice, and chemical quality of rice bran were analyzed using statistical inference method using Analysis of Variance with Completely Randomized Design method. The results showed that the use of Dutch jackfruit leaf flour could still maintain the color and odor quality of rice bran stored for one month. The results of the analysis of variance showed that there was no significant effect of using Dutch jackfruit leaf flour up to a level of 1.8% on the quality of weight, lice, moisture content, ash, crude protein, and crude fat of rice bran.